Internationalization of PY: in-depth analysis of Singapore and LR on international entry mode selection - Estanislau, Anissah Mussa (2022)
PY is a Portuguese SME operating in logistics, offering products (parts and equipment)and services in the maritime industry. The company aims to internationalize and develop an expansion process while being financially constrained. For the internalization plan, an in-depth analysis on the company‘s industry and the market it operates on was developed as the first step of the research. As a result, five potential target countries were selected and studied. Eventually, Singapore was defined as the optimal destination with a contractual agreement entry strategy. Ultimately, a marketing plan and financial forecast were formulated as part of the project‘s implementation strategy.